Immunosuppressant nonadherence profile in kidney transplant recipients and the impact of medication adherence on transplant outcomes - Zhi-yu, Zou; Lin-rui, Dai; Chen-zhen, Yu; Ren-jie, Chen; Fei-hong, Yu; Song, Chen; Sheng, Chang; Wei-jie, Zhang (Frontiers in Pharmacology, 2024)
BackgroundDespite the fact that 1-year graft and recipient survival rates are above 90% in most transplant centers, improving long-term graft survival remains an important challenge. Immunosuppressant nonadherence has been recognized as one of the important risk factors for long-term graft failure. Understanding the modifiable correlates and risk factors for medication non-adherence is essential to develop interventions to improve adherence and thus long-term transplantation outcomes.MethodsThis study conducted a questionnaire survey on 431 renal transplant recipients who were followed up in the outpatient clinic between January 2022 and January 2023, and 409 valid questionnaires were returned. The BAASIS questionnaire was used to assess the prevalence of nonadherence to immunosuppressive therapy (implementation phase) in Chinese renal transplant recipients and to explore the multilevel correlates of immunosuppressive nonadherence. The BAASIS questionnaire was used to categorize renal transplant recipients into adherent (n = 239) and non-adherent (n = 170) groups, and a prospective cohort study with a 1-year follow-up was conducted to explore the impact of immunosuppressant non-adherence on clinical outcomes.ResultsThe prevalence of nonadherence to immunosuppressant therapy in renal transplant recipients in this study was as high as 41.6%. The number of years post-transplant (OR: 1.240, 95% CI: 1.136–1.353, p < 0.001) and the frequency of twice-daily dosing (OR: 5.145, 95% CI: 2.690–9.840, p < 0.001) were positively correlated with immunosuppressive nonadherence. There was a significant difference in TAC IPV (Intra-individual Variability) between the adherent and nonadherent groups (22.7 ± 8.7 vs. 25.4 ± 11.6, p = 0.010). Renal function remained stable during the follow-up period in the recipients in the adherence group and tended to decrease in the recipients in the non-adherence group (F = 4.932, p = 0.001). The rates of graft loss (7.1% vs. 1.7%, p = 0.006) and rejection (12.4% vs. 4.2%, p = 0.002) were higher in the nonadherent group than in the adherent group.ConclusionLonger time post-transplant and higher frequency of immunosuppressive dosing were positively associated with nonadherence to immunosuppressives medication. Immunosuppressant nonadherence was associated with adverse graft outcomes.